The use of animal for scientific purposes in Malaysia: Law, policy and implementation - Intan Shafinaz binti Mohammadi
This research is an evaluative study on the use of animals for scientific purposes i.e. research, testing and teaching in Malaysia. Animal has been used for the benefit of human beings including subjected to scientific purposes since decades ago. In Malaysia, we have used animals for research since the establishment of Institute for Medical Research (IMR) in Kuala Lumpur in the early 1950s. However, the law governing the use of animal in science in Malaysia is inadequate. Proposal to establish an animal laboratory in Melaka in 2010 where trial medicine was suggested to be tested in animals invites immense outcry from the public as well as related non-governmental organization (NGOs). Furthermore , reported news of the existence of a laboratory in Penang without a permit from authority alarming to the need of a law that governs the subject matter. In response to the issues, the government proposed new legislation regulating animal welfare i.e. Animal Welfare Act 2015 among others to bring importance significant in regulating the use of animal in research. Thus, this research discusses first the animal welfare concept from different perspectives i.e. moral, scientific, international and Islamic. Then, it analyses the Malaysia laws and policies regulating the subject matter as well as how the law is implemented in the country. This study adopts both doctrinal and non-doctrinal research. Doctrinal research is considered by looking at the primary and secondary sources of law. Primary sources of law i.e. federal law and policies, international law, custom and religious perspectives are referred. Furthermore, this study also makes reference to secondary sources of law such as books, journal, databases and internet site of relevant organizations to inform the data. This research will also adopt non-doctrinal approach which considers qualitative method. It involves interviews, focus group discussion and observation. The informants that relevant to this research are from various departments and institutions such as Department of Veterinary Services (DVS),Institute of Medical Research (IMR), Laboratory Animal Science Association Malaysia (LASAM), PERHILITAN, Society for the Prevention of Cruelty to Animal (SPCA) of Selangor and universities. This research provides an overview on the Malaysian law governing the use of animal for scientific purposes as well as contributes to the literature in the area concerned. This research suggests that Malaysian legislation is based on animal welfare concept that permits animals to be used for scientific purposes only if the requirements of law governing the subject matter are adhered.